Keputusan Penerjemahan dalam Lokalisasi Website - Nugraha, Anandika Panca (Kementerian Sekretariat Negara Republik Indonesia, 2024)
Web localization is not merely to translate the content or information contained within a website, but also how to customize it to make it acceptable and readable for the target audience. In doing so, translators need to recognize the preliminary aspects such as website type or purpose, target audience, and client’s instruction. On these bases, translators must then make translation judgments, whether certain elements should be translated. This article is qualitative descriptive research which expounds the reasons behind translators' decision to translate or not to translate parts of text in website localization process. The data were taken from 4 English source websites and their Indonesian versions. The findings show that the translators decide to translate parts of the source text to adapt to the source website type and the target audience. The translators decide not to translate some parts of the text due to some factors: website type or purpose, target audience, client’s instruction, and space availability. Therefore, it is suggested that those aspects must be heeded by any website translators so as to make their translation have better readability among the intended readers. Keywords: translatability, website localization, client instruction, audience, translator’s decision